(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
ABSTRACT: Starting from the hermeneutic value played by the veil issue in analyzing the contemporary dynamics of the right to religious freedom in Europe, the paper will focus on the tension between the modern and contemporary paradigm of this right: a tension that makes its effects felt on the broader Mediterranean scale and that hints at new scenarios of a postmodern European right to religious freedom. SOMMARIO: 1. Introduction - 2. Separation: The Matrix of Freedom of Religion as a Right of Modernity - 3. Islam and Separation: Modernity Stumbles - 4. A Broader Scenario: The Mediterranean Backdrop - 5. Prospects for a Post-modern Right to Freedom of Religion.